Role of a Highly Conserved NH(2)-Terminal Domain of the Human Parainfluenza Virus Type 3 RNA Polymerase - Malur, Achut G. (American Society for Microbiology, 2002)
The RNA polymerase complex of human parainfluenza virus type 3 (HPIV 3), a member of the family Paramyxoviridae, is composed of two virally encoded polypeptides: a multifunctional large protein (L, 255 kDa) and a phosphoprotein (P, 90 kDa). From extensive deduced amino acid sequence analyses of the cDNA clones of a number of L proteins of nonsegmented negative-strand RNA viruses, a cluster of high-homology sequence segments have been identified within the body of the L proteins. Here, we have focused on the NH(2)-terminal domain of HPIV 3 L protein that is also highly conserved. Following mutational analyses within this domain, we examined the ability of the mutant L proteins to (i) transcribe an HPIV 3 minireplicon, (ii) transcribe the viral RNA in vitro using the HPIV 3 nucleocapsid RNA template, and (iii) interact with HPIV 3 P protein. Our results demonstrate that the first 15 amino acids of the NH(2)-terminal domain spanning a highly conserved motif is directly involved in transcription of the genome RNA and in forming a functional complex with the P protein. Substitution of eight nonconserved amino acids within this domain by the corresponding Sendai virus L protein residues yielded mutants with variable transcriptional activities. However, one mutant in which all eight amino acids were replaced with the corresponding residues of Sendai virus L protein failed to both transcribe the minireplicon and interact with HPIV 3 P and the Sendai virus P protein. The possible functional significance of the NH(2)-terminal domain of paramyxovirus L protein is discussed.